2013
DOI: 10.1002/ccd.24562
|View full text |Cite
|
Sign up to set email alerts
|

Repeat balloon aortic valvuloplasty effectively delays surgical intervention in children with recurrent aortic stenosis

Abstract: BAV2 is associated with decreased valve gradient, though with an increase in AI. However, residual AS, not AI, is associated with poor outcomes following BAV2. BAV2 effectively treats recurrent AS and postpones need for surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…These findings are in line with the literature [1,6,9]. Nevertheless, a second intervention (either surgery or BAV-36 % in our series) appeared unavoidable in a third of patients in the long term [7,12,13]. The mortality rate was 11.8 % for the whole cohort and 27 % for the neonate subgroup.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with the literature [1,6,9]. Nevertheless, a second intervention (either surgery or BAV-36 % in our series) appeared unavoidable in a third of patients in the long term [7,12,13]. The mortality rate was 11.8 % for the whole cohort and 27 % for the neonate subgroup.…”
Section: Discussionsupporting
confidence: 93%
“…The results were comparable to surgical valvotomy (4). This was further correlated by Justino and the group at Texas Children’s Hospital who found that repeat AoVP effectively treats recurrent AS and postpones the need for surgical intervention (5). …”
Section: Discussionmentioning
confidence: 83%
“…that describes outcome of balloon dilatation after surgical valvotomy in 23 children. 23 They suggest that reintervention with balloon valvotomy is both effective in relieving stenosis and delays further surgical interventions. Our experience is that surgical valvotomy as primary treatment has definite advantages but, in this setting, balloon valvotomy may be a good option, as a less invasive procedure, for reintervention to postpone aortic valve replacement.…”
Section: Discussionmentioning
confidence: 99%